(untitled) (Journal of Global Economics & Sustainable Development, 2025)
This study examines the complex relationship between sustainable finance mechanisms and climate change mitigation effectiveness through a comprehensive analysis of green bonds, Environmental, Social, and Governance (ESG) investing, carbon markets, climate risk assessment, and sustainable banking practices. Using empirical evidence from 2020-2025, we find that sustainable finance demonstrates measurable but limited climate impact, with green bonds achieving 4-16% emissions reductions and ESG investing showing positive financial returns in 60-90% of studies, though significant gaps remain between current financing scales (2.1 trillion annually) and required climate investment needs (5.6 trillion annually through 2030). The analysis reveals that third-party certification, regulatory standardization, and public-private partnerships are critical success factors, while political pressures and measurement challenges limit effectiveness, with geographic inequality representing a fundamental barrier as 95% of sustainable finance concentrates in developed economies despite emerging markets representing the majority of future emissions growth. Our findings suggest that sustainable finance mechanisms require enhanced governance frameworks and policy coordination to achieve transformational climate impact at the scale and speed demanded by the Paris Agreement goals, moving beyond voluntary approaches toward comprehensive regulatory frameworks that address market integrity challenges, including greenwashing and quality concerns in voluntary carbon markets. The research synthesizes findings from over 40 recent peer-reviewed studies and provides evidence-based policy recommendations for scaling climate finance while maintaining market integrity, highlighting that while current sustainable finance flows demonstrate potential effectiveness, realizing this potential at required scale depends on decisive policy action, enhanced international cooperation, and continued innovation in financial mechanisms and regulatory approaches.